Pomiar i testowanie skośności rozkładów stóp zwrotu instrumentów finansowych - Piontek, Krzysztof (Measuring and Testing of Skewness for Financial Return Distributions, 2007)
The presumption of skewness in financial returns is implicitly or explicitly assumed in many financial models. However, the possible skewness of the unconditional distribution of stock or index returns is still an open question. In this paper, three different approaches are briefly reviewed and their properties discussed in the relevance of testing skewness in the whole return distribution: the adjusted Jacque- Bera test, the test based on the GARCH(1,1) model with the conditional Pearson type IV distribution and the distribution free test for skewness by Peiro. In the empirical part of the paper, 150 Polish financial series are examined. The results received from our research proved that about 42% of financial distributions are asymmetric.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 122-130